Dependence of Acute Myeloid Leukemia on Adhesion within the Bone Marrow Microenvironment - Pamela S. Becker (The Scientific World Journal)
Acute myeloid leukemia (AML) cells home to the endosteal region of the bone marrow. They interact with bone marrow stromal components including extracellular matrix proteins, glycosaminoglycans, and stromal cells, by which they derive proliferative and growth inhibitory signals. Furthermore, adhesion to marrow stroma confers chemotherapy drug resistance and thereby promotes leukemia survival. A subpopulation of the leukemic blasts, known as leukemia stem cells, that are capable of propagating the leukemia, remain sheltered in the bone marrow microenvironment, exhibit resistance to chemotherapy, and serve as the origin of relapse after a variable period of remission. Detachment of these cells from the bone marrow in combination with chemotherapy may improve the outcome of therapy for AML.